PERILAKU MAHASISWA DALAM MENGGUNAKAN MEDIA SOSIAL DI UNIVERSITAS SAM RATULANGI MANADO - Drakel, Wahyuni Januarti; Pratiknjo, Maria Heny; Mulianti, Titiek (HOLISTIK, Journal Of Social and Culture, 2018)
Social media presence and the sophistication of information technologies are indeed often referred to as a symbol of the progress of human thinking. Without conscious media has brought logging to the new cultural patterns and begin to determine the mindset and behaviour in society. Surely media in social life is not simply a means of diversion, a tension reliever or entertainment, but the content and the information presented, has a significant role in the process of social change. Changes in the pattern of behavior is most noticeably is the aspect of lifestyle and this aspect is most visible in the environment of the young generation in particular Sam Ratulangi University students.This research used the qualitative method, a method of describing a phenomenon in accordance with the topics researched. Qualitative research or often called naturalistic research, i.e., the methods used to examine the conditions of natural objects (as his opponent is an experiment) where researchers is a key instrument.Felt the presence of the student lifestyle changes which often have wasted time and the increasing number of negative content are popping up in social media. Along with the development of the era, the use of the internet is getting sued. As a result it is now more and more social media types that are used by the student. For example, namely Facebook, Line, Path, Whatsapp and Instagram. It all goes back to a personal, how can one addressing the development of current media and know the positioning of the function of social media according to existing rules and conditions are primarily college students because the students had said when someone means already in top students, he should be able to tell which is a good thing to do and not do. A student must be able to hone his thinking way for more critical.Keywords: top student, social media, behavioral